The fiscal dimensions of conflict and reconstruction - Tony Addison; S. Mansoob Murshed (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Political violence, coup d'état, civil wars and inter-state wars, all have fiscal dimensions (and sometimes fiscal causes). Who gets what—public employment and public spending—and who has to pay for it, are questions that raise fundamental issues about the distribution of society's resources. These can only be resolved peacefully by some form of social contract, resting on the foundation of effective fiscal institutions (systems of public spending and taxation). Accordingly, the paper contrasts the evolution of fiscal institutions in stable and unstable societies. The paper discusses the likelihood of a fiscal peace dividend, but notes that `incomplete' peace—and therefore the continuation of high levels of military spending—limits the scale of the dividend in many cases. Broad reconstruction from war—which spreads its benefits widely so that poverty is reduced—is contrasted with narrow reconstruction, in which society's elite may consolidate their war-time gains, but in which the majority are left behind. Effective fiscal institutions are critical to determining whether broad or narrow reconstruction takes place. The paper concludes by emphasising the need to better understand the incentives of governments to improve fiscal institutions, and the role that conflict has in affecting their motivation. – conflict ; fiscal policy ; sub-Saharan Africa
Keywords: H56; O15; D30; 330; Öffentliche Finanzwirtschaft; Zentralafrika; Politischer Konflikt